More Similar to My Father, Better Academic Performance I Will Have: The Role of Caring Parenting Style - Tu M; Guo Y; Zhang X; Yu Q (Psychology Research and Behavior Management, 2021)
Mengjie Tu,1 Yafei Guo,2 Xincai Zhang,3 Quanlei Yu1,4 1School of Psychology, Central China Normal University, Wuhan, Hubei, People’s Republic of China; 2Department of Business Administration, University of Illinois at Urbana-Champaign, Champaign, IL, USA; 3Fuyang City No.11 Middle School, Anhui, People’s Republic of China; 4School of Psychology, Beijing Normal University, Beijing, People’s Republic of ChinaCorrespondence: Quanlei Yu Email yulei19881987@mail.ccnu.edu.cnBackground: Parent-child facial resemblance, as an important cue of paternal uncertainty, may impact fathers’ parenting behaviors and further affect children’s academic performance. However, mothers are almost 100% confident of the blood relationship with their child and care less about the facial resemblance cues.Methods: To test these hypotheses, the present study recruited 122 junior high school students and measured the perceived facial resemblance with their parents, the parents’ parenting style, academic performance, and demographic variables.Results: The results showed that the perceived father-child facial resemblance rather than the mother-child facial resemblance significantly influenced adolescents’ academic performance. Further, fathers’ caring parenting style mediated the relationship between the perceived father-child facial resemblance and academic performance.Conclusion: These findings not only supported the paternal uncertainty hypothesis but also extended the parental investment theory.Keywords: perceived father–child facial resemblance, academic performance, caring parenting, paternal uncertainty